Modification of the existing maximum residue levels for isofetamid in raspberries, blackberries and dewberries - EFSA (European Food Safety Authority); Giulia Bellisai; Giovanni Bernasconi; Alba Brancato; Luis Carrasco Cabrera; Lucien Ferreira; German Giner; Luna Greco; Samira Jarrah; Aija Kazocina; Renata Leuschner; Jose Oriol Magrans; et al. (EFSA Journal, 2021)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant ISK Biosciences Europe N.V. submitted a request to the competent national authority in Belgium to modify the existing maximum residue levels (MRLs) for the active substance isofetamid in raspberries, blackberries and dewberries. The data submitted in support of the request were found to be sufficient to derive MRL proposals for blackberries, dewberries and raspberries. Adequate analytical methods for enforcement are available to control the residues of isofetamid in the commodities under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of isofetamid according to the reported agricultural practices is unlikely to present a risk to consumer health.